2018
DOI: 10.1534/g3.118.200368
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Quantitative Trait Loci for Tolerance to Pythium irregulare in Soybean (Glycine max L.)

Abstract: Pythium root rot is one of the significant diseases of soybean (Glycine max (L.) Merr.) in the United States. The causal agent of the disease is a soil-borne oomycete pathogen Pythium irregulare, the most prevalent and aggressive species of Pythium in North Central United States. However, few studies have been conducted in soybean for the identification of quantitative trait loci (QTL) for tolerance to P. irregulare. In this study, two recombinant inbred line (RIL) populations (designated as POP1 and POP2) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…irregulare are new compared with those reported from two previous studies (Ellis et al, 2013;Stasko et al, 2016). However, there is one potential overlap with chromosome 11 recently reported by Lin et al (2018) from Michigan breeding line E09088. In this study and the previous reports, the identified QDRL were minor, with the exception of QDRL on chromosome 13 (BARC-900926-00961), which explained 17.7% of the phenotypic variance in a cross with Dennison (Ellis et al, 2013).…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…irregulare are new compared with those reported from two previous studies (Ellis et al, 2013;Stasko et al, 2016). However, there is one potential overlap with chromosome 11 recently reported by Lin et al (2018) from Michigan breeding line E09088. In this study and the previous reports, the identified QDRL were minor, with the exception of QDRL on chromosome 13 (BARC-900926-00961), which explained 17.7% of the phenotypic variance in a cross with Dennison (Ellis et al, 2013).…”
Section: Discussionmentioning
confidence: 43%
“…Comparison of major and minor quantitative disease resistance loci (QDRL) to Py. However, there is one potential overlap with chromosome 11 recently reported by Lin et al (2018) from Michigan breeding line E09088. sporangiiferum significant at the genome-wide threshold mapped in the nested association mapping (NAM) recombinant inbred line (RIL) population generated from the cross of IA3023 ´ LG05-4832.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations